Physical Intimate Partner Violence in Pregnant Women and its Risk on Low Birth Weight: A Meta-Analysis - Nawangwulan, Diyah; Murti, Bhisma; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2024)
Background: Intimate Partner Violence (IPV) is a significant public health problem that affects women, including pregnant women. During pregnancy, pregnant women experiencing IPV will have an impact on the health of the mother and fetus, including an increased risk of premature birth and low birth weight babies. This study aims to analyze and estimate the influence of physical intimate partner violence in pregnant women on low birth weight infants. Subjects and Method: Meta-analysis was carried out according to the PRISMA flow diagram and PICO Model. Population: pregnant women, Intervention: Intimate partner violence, Comparison: No intimate partner violence, Outcome: low birth weight babies. Search for articles in this research through databases including PubMed, Google Scholar, ScienceDirect by selecting articles published in 2015-2023. With the keywords "Intimate Partner Violence" OR "Domestic Violence" AND "Low Birth Weight" AND "Pregnancy" AND "Adjusted Odds Ratio". Inclusion criteria are full paper articles with an observational study design, articles are in English. Results: Nine studies of cohort and cross-sectionals were included for meta-analysis. Meta-analysis of 5 cohort studies showed that physical intimate partner violence in pregnant women increased the risk of infants low birth weight (aOR= 3.66; 95% CI= 2.31 to 5.79; p<0.001). Meta-analysis of 4 cross-sectional studies showed that physical intimate partner violence in pregnant women increased the risk of infants low birth weight (aOR= 3.60; 95% CI= 2.05 to 6.32; p< 0.001). Conclusion: Physical intimate partner violence in pregnant women increases the risk of infants with low birth weight.